Variability between domestic buildings: the impact on energy use. Issue 2 (3rd March 2016) - Evins, Ralph; Orehounig, Kristina; Dorer, Viktor
Abstract : Variations in operational use (in the time domain) and in design and use (between buildings) are critical for district systems. The effects on energy use of behavioural (stochastic profiles of occupancy and end uses) and physical variations (size, orientation, insulation and air tightness) amongst many buildings is examined. Rather than investigating just the variability of these factors, the aim is to identify subsequent impacts on building energy use. To achieve this, dynamic building energy simulations in EnergyPlus are performed. Results include total demands and their distributions, and temporal and probabilistic profiles. Very large variations in total heating demand are noted. Temporal profiles show changes in peak loads, load durations and periods of zero load. Probabilistic profiles and cumulative distributions show that a few buildings are responsible for the majority of total loads. Full detailed simulations are identified as critical when assessing temporal effects such as peak loads and storage sizing.